Geneologi Tradisi Ilmiah Navigasi Bugis: Studi Historis Perkembangan Navigasi Bugis dalam Astronomi Islam - Fathur Rahman Basir; Nur Aisyah Nur Aisyah (HISABUNA: Jurnal Ilmu Falak, 2020)
Navigation in general is directing a ship on a voyage or a way to determine the position and direction of travel both on the actual terrain and on the map. Shipping activities are seen as a medium of community communication in one region with other regions. Bugis tribe is one of the nations of the archipelago that is oriented to the sea, and many create a tradition and culture in shipping activities. This journal discusses the roots of bugis navigation in the 17th century that marked the development of Islamic civilization in the midst of the culture of Bugis society. The 17th century in a Bugis society was an era where Islam and culture were integrated but remained in accordance with Islamic values. This can be found in ancient manuscripts sourced from the literature of the Buginese community. The journal also shows that before the advent of modern navigation tools, Bugis sailors relied on their ability and experience to sail, utilizing natural phenomena both in the sky and at sea. Like using the wind, moon, and stars.